The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/php.12349
|View full text |Cite
|
Sign up to set email alerts
|

Sun Exposure and Vitamin D Status as Northeast Asian Migrants Become Acculturated to Life in Australia

Abstract: Vitamin D deficiency is more common in Northeast-Asian immigrants to western countries than in the local population; prevalence equalizes as immigrants adopt the host country's culture. In a community-based study of 100 Northeast-Asian immigrants in Canberra, Australia, we examined predictors of vitamin D status, its association with indicators of acculturation (English language use; time since migration) and mediators of that association. Participants completed a sun and physical activity diary and wore an el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…However, 5 hours might be a high cut-off value for sun exposure time, considering the result that 64% of Northeast Asian Austrians aged 18 to 80 years reported less than 1 hour of daily sun exposure. 42 In the current study, more than 92% of the subjects reported less than 5 hours of daily sun exposure on average. The reasons for low sun exposure time might be associated with the characteristics of the participants in this study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, 5 hours might be a high cut-off value for sun exposure time, considering the result that 64% of Northeast Asian Austrians aged 18 to 80 years reported less than 1 hour of daily sun exposure. 42 In the current study, more than 92% of the subjects reported less than 5 hours of daily sun exposure on average. The reasons for low sun exposure time might be associated with the characteristics of the participants in this study.…”
Section: Discussionmentioning
confidence: 50%
“…First, Asian women tend to avoid direct sun exposure. 42,43 Second, subjects with cataracts or a history of cataract surgery, which can considerably influence refractive error, were excluded in this study. This could have affected the low sun exposure time in this data set, as sun exposure is an important risk factor for cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is matched by cross-sectional studies in Queenslanders that found: '25(OH)D levels were also lower in participants who had black hair, dark/olive skin, or brown eyes, when compared with participants who had brown or fair hair, fair skin, or blue/green eyes' (22) . A host of additional studies from different locations have confirmed a significant skin-colour differential in circulating 25(OH)D (27)(28)(29)(30)(31)(32) , whereas a substantial number have failed to confirm this finding (33)(34)(35)(36)(37)(38)(39) .…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of this study include the use of dairies for daily sun exposure and the categories of sun protection behaviors collected. Other studies using sun exposure and sun protection diaries have only collected information for periods of several days to a week. The longer duration provided more stable estimates.…”
Section: Discussionmentioning
confidence: 99%